Selective Inhibitors of FKBP51 Employ Conformational Selection of Dynamic Invisible States. (5th June 2019) - Jagtap, Pravin Kumar Ankush; Asami, Sam; Sippel, Claudia; Kaila, Ville R. I.; Hausch, Felix; Sattler, Michael
Abstract: The recently discovered SAFit class of inhibitors against the Hsp90 co‐chaperone FKBP51 show greater than 10 000‐fold selectivity over its closely related paralogue FKBP52. However, the mechanism underlying this selectivity remained unknown. By combining NMR spectroscopy, biophysical and computational methods with mutational analysis, we show that the SAFit molecules bind to a transient pocket in FKBP51. This represents a weakly populated conformation resembling the inhibitor‐bound state of FKBP51, suggesting conformational selection rather than induced fit as the major binding mechanism. The inhibitor‐bound conformation of FKBP51 is stabilized by an allosteric network of residues located away from the inhibitor‐binding site. These residues stabilize the Phe67 side chain in a dynamic outward conformation and are distinct in FKBP52, thus rationalizing the basis for the selectivity of SAFit inhibitors. Our results represent a paradigm for the selective inhibition of transient binding pockets. Abstract : Der FKBP51‐Inhibitor SAFit1 bindet eine wenig populierte Konformation von FKBP51, bei der Phe67 im ungebundenen Zustand nach außen gerichtet vorliegt. Dies deutet darauf hin, dass SAFit1 über Konformationsselektion anstelle eines „induced fit" an FKBP51 bindet. Die Stabilisierung von Phe67 in dieser dynamischen nach außen gerichteten Konformation beruht auf Wechselwirkungen mit FKBP51‐spezifischen Resten, was die Selektivität für FKBP51 vs. FKBP52 erklärt. Dies zeigt die Bedeutung von Proteindynamik für das Design selektiver Inhibitoren.